Characterization and Geological Implications of Precambrian Calcite‐Hosted Phosphate. Issue 17 (10th September 2022) - Richardson, Jocelyn A.; Roest‐Ellis, Sascha; Phillips, Brian L.; Strauss, Justin V.; Webb, Samuel M.; Tosca, Nicholas J.
Abstract: Constraints on marine phosphate availability and cycling directly inform our understanding of long‐term biological evolution. However, early Earth phosphate records are sparse, biased toward siliciclastic samples, and susceptible to post‐depositional modification. Well‐preserved shallow marine inorganic carbonate precipitates provide a complementary yet understudied record of phosphate cycling. We combined micro‐X‐ray fluorescence mapping, X‐ray absorption, and Nuclear Magnetic Resonance spectroscopy on samples of Precambrian syndepositional herringbone calcite (HBC) and microspar to characterize phosphorus speciation and distribution in these carbonate fabrics. Phosphorus spectroscopy from synthetic calcite, HBC, and microspar, is qualitatively consistent with a disordered distribution of phosphate. These characteristics are diagnostic of calcite‐hosted phosphate, which is pervasive at low concentrations in HBC and microspar. This study provides evidence that ancient, well‐preserved carbonate fabrics retain phosphate sourced from seawater and highlights the potential for an unaltered archive of marine phosphate concentration over geologic time. Plain Language Summary: Phosphorus is a critical nutrient to sustain life on Earth as we know it. Understanding the form and source of phosphorus on the early Earth will enhance our knowledge of the origins and early evolution of life. However, there is no way to directly measure the source, form and abundance of phosphorus in the environment when life was evolving over 2.5 billion years ago. The rock record provides a potential archive to indirectly measure phosphorus from ancient marine environments, yet there are a number of considerations, for example; (a) which minerals are able to record information about marine phosphorus? (b) How do we know those minerals have not been altered over time? In this work, we have identified well‐preserved, unaltered carbonate minerals from ∼2.5 billion and 800 million years ago, that preserve marine phosphate within their mineral structure using micron‐scale techniques. The characterization of this form of phosphorus is important to our understanding of the evolution of the phosphorus cycle over Earth's history. Key Points: Synchrotron analyses identify calcite‐hosted phosphate in well‐preserved Precambrian carbonate fabrics Herringbone calcite and synsedimentary microspar serve as an unaltered archive for ancient marine dissolved inorganic phosphate Micrite retains abundant apatite mineral micro‐inclusions that may bias bulk calcite‐hosted phosphate or P/Ca records